The role of L1 literacy and reading habits on the L2 achievement of adult learners of English as a foreign language. (June 2017) - Artieda, Gemma
Abstract: This study examines the impact of L1 literacy and reading habits on the L2 achievement of two groups of bilingual adult learners of EFL (52 beginners, 88 intermediate) in a language school with low L1 literacy students. Participants were tested on two L1 literacy measures (L1 reading comprehension, L1 spelling), on L2 achievement, and reported on two reading habits measures: reading quantity and enjoy reading. Results for the beginner group suggest that L1 literacy acts as a threshold to L2 achievement for academically disadvantaged learners, and provide evidence of the enduring influence of early L1 literacy skills on L2 achievement in adulthood. Conversely, for intermediate students, reading habits is the only literacy-related factor impacting L2 outcomes. The study concludes that educators need some awareness of adult EFL learners' L1 literacy level to help them achieve their language learning goals.